HOSPITAL READINESS TO IMPLEMENT ELECTRONIC MEDICAL RECORDS: A SYSTEMATIC LITERATURE REVIEW - Fatmasari, Afni; Nadjib, Mardiati (UI Scholars Hub, 2024)
Implementing electronic medical records (EMR) in hospitals can increase the efficiency and effectiveness of health services. However, hospitals' readiness to adopt this technology is influenced by various complex factors. This study aims to identify factors that affect hospital readiness in implementing EMR through a systematic literature review (SLR). The SLR process followed the PRISMA method and included a literature search from Scopus, PubMed, and Cochrane databases with keywords related to RME readiness, which yielded 412 articles. After the screening and eligibility stages, 19 articles were selected for further analysis. The findings of this research identify readiness factors based on the theory of technology organization and environment (TOE). In the context of technology, factors such as technology access, perceived benefits, perceived usefulness, and performance expectancy emerge as important determinants of readiness. In an organizational context, management support, organizational culture, computer competency, and knowledge of EMR are key factors. Meanwhile, societal influence and environmental conditions play a significant role in the environmental context. These findings provide valuable insights for policymakers and hospital management in designing strategies to increase RME adoption readiness. This research has limitations in geographic and language coverage and the use of a single database. Therefore, further research is needed to broaden the scope and deepen understanding of the interactions between various readiness factors.